Development of a framework for supply chain 4.0 - Anjaya, Jillian Ivory (Nanyang Technological University, 2025)
The rise of Industry 4.0 trends and technologies has caused disruptions within modern-day supply chains, affecting not only the way in which they conduct their operations but also the products and services that they produce. As a result, companies must adapt their supply chains to withstand these disruptions and mitigate the disastrous effects they may potentially have in the future,. This presents a need for an updated supply chain model that companies can refer to when transforming their supply chains to be better adapted to the current industrial age.. This paper documents the development of a framework for Supply Chain 4.0 that companies can utilise as reference to modify their supply chains accordingly.